Boredom in workplace and its relationship to life satisfaction among recreation and leisure professionals - Joohyun Lee; Zack Wetzel (Tourism & Management Studies)
This study examined the relationship between job boredom and life satisfaction among recreation and leisure professionals. Data was collected from 365 members of Florida Recreation and Parks Association. A set of regression analyses were used to find out if job boredom improved prediction of life satisfaction and differences in demographic variables among recreation and leisure professionals. The findings suggest that job boredom is a negative predictor of life satisfaction. Age and year in recreation profession were significantly related to job boredom of recreation and leisure professionals. Suggestions were made based on the results of the study.